IMPLEMENTASI STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) UNTUK MENINGKATKAN KEMAMPUAN KERJA SAMA SISWA KELAS IV SD - Multisarita; Muhammad Jamhari; Isrofiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to examine the effectiveness of implementing the Student Teams Achievement Divisions (STAD) learning model in improving the cooperative skills of fourth-grade students at SDN 12 Palu. The study employs a Classroom Action Research (CAR) approach consisting of four stages: planning, action/implementation, observation, and reflection. The research subjects were 23 students from Class IVB who participated in cooperative learning using the STAD method. Data were collected through observations over three sessions, using observation sheets to assess five aspects of collaborative skills: contribution, time management, problem-solving, working with others, and investigation techniques. The results of the study indicate a significant improvement in each aspect of cooperative skills following the implementation of STAD. The average scores for contribution increased from 2.89 to 3.46, time management from 2.66 to 3.29, problem-solving from 2.38 to 3.31, working with others from 2.92 to 3.23, and investigation techniques from 2.13 to 3.23. These findings suggest that the STAD model can enhance students' cooperative skills at the elementary school level. This research also reinforces previous findings, which state that STAD is not only effective in improving academic achievement but also in developing students' social and emotional skills. Therefore, implementing STAD can serve as an effective alternative to improving the quality of learning in elementary school classrooms.